The Contributions of Industrial Hygiene in Occupational Ergonomics - Sherif Ibrahim (Journal of Architecture, Art & Humanistic Science, 2019)
This summary reviews the general features and results of the research, entitled " The Contributions of Industrial Hygiene in Occupational Ergonomics ", and is about clarifying the role of Industrial Hygiene as one of the occupational health and safety sciences specialized in the expectation of exposure to risks of different types of workplaces and Also study and analyze the method of entering the damage to the human body and its effect on the internal organs and sensory damage. What distinguishes this science is to anticipate exposure or damage to humans in the workplace through the application of mechanisms of the process of anticipation. With the development of manufacturing technology and its dependence on systems in the management and manufacturing processes, there are many renewable and diversified workplace hazards that affect human health and production efficiency. As a result, the Occupational Ergonomics has emerged as a specialized science in studying ergonomics Environment, Software, Systems, Workplace Components, Identifying the sciences and disciplines required to study their risks, and finding solutions through the applied side of this science, the Occupational Ergonomics Program. This research reviews the contributions and role that Industrial Hygiene can achieve through its stages and specialized in the applications of the scientific knowledge of Ergonomics through information and mechanisms by:- To support the types of Occupational Ergonomics experience with medical information about the senses and internal organs of the body and the impact of exposure to damage to them.- Incorporation of predictive or predictive mechanisms of risk in macro ergonomics methods specialized in studying systems, their interactions and their impact on humans.- Contribute to the Occupational Ergonomics program by the specialists , and supporting all stages of data and information.